Tema-Tema Besar Pemikiran Muhammad al-Ghazali - Ghazali, Mohd Rumaizuddin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
This article discusses the biography of Muhammad al-Ghazali, a famous ulama from Egypt. He has authored more than 60 books on many aspects of Islam. Among the main themes which often discusses are the correct process of interaction with the al-Qur'an, the status of women, the status of tasawuf, and the development of civilizations. He stresses that it is important for Muslims to adhere strictly to the teaching of the al-Qur'an as the basis for achieving success and progress.